Draft Annual Plan 1986-87 Volume XIV Ladakh Sub-Plan Jammu and Kashmir Government - Planning Commission (Planning Commission, 1985)
For meeting the committed liability of agriculture farms at Thiksay, Balam, Terchey an amount of Rs. 0.81 lacs has been proposes. Rs. 0.05 lacs have been proposed for to the completion of ongoing work at Terchey.
Jammu and Kashmir Government, Planning and Development Department